Impact Of Threats On The Prosperity Of Automotive Industry: An Exploratory Study Based On Malaysia - et. al., DR. Amiya Bhaumik, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Located in South-East Asia, the country takes into account costs and bargains competitively in the importation of non-landed process outputs that are vital to the process of vehicle manufacturing in both regional and global markets. The business-friendly Malaysian economy is reinforced by a free-market approach Germany is Malaysia's second largest trade partner among the ASEAN nations. The vehicles produced in Germany and sold in Malaysia form the majority of the country's total sales, while automobile component exports amount to a significant amounts in Malaysia. Many German automakers have historically entered the Malaysian market, but few of them do so today. Affiliated corporations, such as BMW and Mercedes-Benz, implement program amenities such as a delivery service like that Trade-only depictions will not come from conventional partners but will be re-destined to traditional partners. There was an impressive delivery of varieties, such as BMWs and Mercedes, for instance. The upcoming liberalization of Malaysian manufacturing is predictable, and indigenous firms have no choice but to take action to change everything they can to reduce costs. To cater for rising demand, minding any topic problems necessitates wide-ranging competencies. Furthermore, considerable investment in spotless serviceable vigor has been invested in by the automakers, and non-automotive divisions have achieved prominence. rapid and relevant conversations are made With respect to Malaysia, a formal research has been carried out to understand the issues and opportunities faced by the automotive industry The investigation is based on primary and/supported by secondary facts. Stakeholders of the automotive industry were the primary sources of the information. Foreign evidence is used in various publications such as the publications of the car industry, the internet, and online magazines, and business journals as well as well as general trade publications. Found out that the study has shown that, Malaysia is a big producer and exporter of transportation fragments, as well as of additional car buyers. Conclusions and recommendations have been made for this investigation.